2020
DOI: 10.3390/sports8050069
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Workloads of a Professional Female Futsal Team over a Season: A Case Study

Abstract: The aims of this study were to describe the external and internal workloads in a professional female futsal team during a whole season and to compare workloads during different periods of the season. Ten professional female futsal players (age 22.8 ± 4.3 years; 5.1 ± 2.4 years of experience; weight 61.9 ± 7.1 kg; height 1.66 ± 0.06 m) participated voluntarily in this study during the whole season. The internal workload was measured by the session-Rate of perceived exertion (session-RPE) method, while the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
2
11
3
Order By: Relevance
“…Regarding the values mentioned above, we can assume that the S-RPE was considered moderate during the preparatory period. These data are similar to previous studies which were found values between 5 and 6 points on the mean RPE (Teixeira et al, 2018;Lago-Fuentes et al, 2020). So, the present study showed a preparatory period with high volume and moderate intensity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Regarding the values mentioned above, we can assume that the S-RPE was considered moderate during the preparatory period. These data are similar to previous studies which were found values between 5 and 6 points on the mean RPE (Teixeira et al, 2018;Lago-Fuentes et al, 2020). So, the present study showed a preparatory period with high volume and moderate intensity.…”
Section: Discussionsupporting
confidence: 93%
“…It is noted that the training periods are well-defined, even though they have presented different numbers of microcycles between them. As for the preparatory period, it was found that the total ITL does not agree with previous studies that investigated high-level futsal players, such as that of Miloski et al ( 2012 ), and reported higher values of total internal load in the preparatory period. The same pattern of training load distribution was found in another study by Miloski et al ( 2016 ), yet none of them identified which of the variables influenced the training load.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations